Film-coated copper sheet for interconnection of copper electrodes on front surface of chip and preparation method and application of film-coated copper sheet

By interconnecting the front of the chip with coated copper sheets, the problems of surface damage and process complexity during the top bonding of the chip in the prior art are solved, and higher reliability and lower costs are achieved.

CN119560388AActive Publication Date: 2025-03-04BEIJING QINGLIAN TECH CO LTD

Patent Information

Application Number
CN202411450532.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-03-04
Estimated Expiration
2044-10-17

AI Technical Summary

Technical Problem

The prior art can easily cause surface damage during the bonding process of the top copper wire on the chip, which increases reliability risks, and the use of fixatives increases process complexity and affects wiring flexibility.

Method used

The copper electrodes on the front of the chip are interconnected by coating copper sheets. By surface treatment and single-sided metallization of the bare copper sheets, metal solder paste is applied and pre-sintered, and then activated and coated to form a thin and uniform organic protective film.

Benefits of technology

Avoid dispensing fixation, reduce packaging costs, improve service reliability of packaging devices, and maintain electrical and thermal conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005088970210000181
    Figure BDA0005088970210000181
Patent Text Reader

Abstract

The invention provides a film-coated copper sheet for interconnection of copper electrodes on the front side of a chip and a preparation method and application of the film-coated copper sheet. The preparation method comprises the following steps: S1, carrying out surface treatment and single-side metallization treatment on a bare copper sheet to obtain a copper sheet with a single-side metallization layer; s2, the single-face metallization layer of the copper sheet is coated with metal soldering paste, drying is conducted in an inert or reducing atmosphere, and the copper sheet with a pre-sintered metal film is obtained; s3, cleaning, drying and activating the copper sheet to obtain an activated copper sheet; and S4, coating the activated copper sheet with a coating solution, and curing after coating to obtain the film-coated copper sheet for interconnection of the copper electrodes on the front surface of the chip. According to the preparation method, the dried metal soldering paste can be protected, sufficient adhesive force can be provided for the film-coated copper sheet and the chip in the sintering process, dispensing fixation is avoided, the packaging cost is reduced, and the service reliability of a packaged device is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of power device packaging, and in particular to a coated copper sheet used for interconnecting copper electrodes on the front side of a chip, and a preparation method and application thereof. Background Art

[0002] The third generation wide bandgap semiconductors represented by SiC and GaN have excellent working characteristics such as high power density, high junction temperature, and high frequency. The chip top wire bonding, as a packaging structure that provides key electrical connections, faces complex and harsh service conditions, and it is difficult to ensure the long-term stable service of the third generation wide bandgap semiconductor devices.

[0003] In order to improve the reliability of the interconnection on the top of the chip, a copper wire bonding process with high electrical and thermal conductivity, low thermal expansion coefficient and cost-effectiveness has been proposed and promoted. However, due to its high hardness, copper wires usually require strict process specifications and long welding time during bonding, which can easily cause damage to the top surface of the chip and introduce reliability risks.

[0004] In order to solve the above problems, the prior art proposes to use sintered silver as a connecting layer to attach a copper sheet to the top surface of the chip, bond the copper lead to the copper sheet, and use the copper sheet as a buffer layer to protect the chip during the bonding process; wherein, the sintered silver is usually first pre-printed on the copper sheet, and then transferred and assembled to the position to be sintered after drying and connected to the top surface of the chip. In order to ensure the adhesion between the copper sheet and the top surface of the chip and prevent the risk of falling off and shifting during the transfer process, a fixing agent is usually pre-applied to the sintered silver. However, although the above process ensures a stable connection between the copper sheet and the chip, the use of the fixing agent increases the complexity of the sintering process, affects the flexibility of the top wiring (the fixing agent adhesion point needs to be avoided), and the risk of the silver paste falling off on the copper sheet still exists.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a coated copper sheet for interconnecting copper electrodes on the front side of a chip and a preparation method and application thereof, thereby avoiding glue fixation, reducing packaging costs, and improving the service reliability of packaged devices.

[0007] The present invention provides a method for preparing a coated copper sheet for interconnecting copper electrodes on the front side of a chip, comprising the following steps:

[0008] S1: performing surface treatment and single-sided metallization treatment on the bare copper sheet to obtain a copper sheet with a single-sided metallization layer;

[0009] S2: coating a metal solder paste on a single-sided metallization layer of the copper sheet, and then drying it in an inert or reducing atmosphere to obtain a copper sheet with a pre-sintered metal film;

[0010] S3: cleaning, drying and activating the copper sheet with the pre-sintered metal film to obtain an activated copper sheet;

[0011] S4: coating the activated copper sheet with a coating solution, and curing the coated copper sheet to obtain a coated copper sheet for interconnecting the copper electrodes on the front side of the chip.

[0012] In step S1, the material of the bare copper sheet can be oxygen-free copper, red copper, etc. The thickness of the bare copper sheet is 20-200 μm, such as 70-100 μm; the hardness is 70-120 HV, such as 100-120 HV.

[0013] The surface treatment comprises: soaking the bare copper sheet in dilute sulfuric acid solution, anhydrous ethanol and deionized water in turn, repeating for 2-3 times and then drying in an inert atmosphere; wherein the mass content of the dilute sulfuric acid solution is 2-5%, the soaking time of the dilute sulfuric acid solution is 10-15 minutes; the soaking time of the anhydrous ethanol is 3-5 minutes; the soaking time of the deionized water is 3-5 minutes; the inert atmosphere is a nitrogen atmosphere, the drying temperature is 40-60°C, and the drying time is 20-40 minutes.

[0014] The single-sided metallization treatment includes: forming a single-sided metallization layer on the surface of the bare copper sheet after surface treatment, the single-sided metallization layer is Ag plating, Ni / Ag plating or Ni / Pd / Au plating, and the thickness of the single-sided metallization layer is 1-3 μm; the Ni / Ag plating includes a Ni plating layer and an Ag plating layer sequentially arranged on the surface of the bare copper sheet, and the thickness ratio of the Ni plating layer to the Ag plating layer is (1.5-2.5):1, for example, 2:1; the Ni / Pd / Au plating includes a Ni plating layer, a Pd plating layer and an Au plating layer sequentially arranged on the surface of the bare copper sheet, and the thickness ratio between the Ni plating layer, the Pd plating layer and the Au plating layer is (1.5-2):(0.1-0.5):1, for example, 1.8:0.2:1. Providing the above-mentioned single-sided metallization layer on the surface of the bare copper sheet is conducive to improving the adhesion between the metal film and the copper sheet.

[0015] In step S2, the method for preparing the metal solder paste comprises the following steps:

[0016] a1) performing a deoxidation treatment on the metal particles to obtain deoxidized metal particles;

[0017] b1) mixing the deoxidized metal particles, the corrosion inhibitor and the organic solvent, ultrasonicating, centrifuging and washing to obtain the corrosion inhibitor-coated metal particles;

[0018] c1) mixing an antioxidant and an organic solvent and stirring to obtain an organic solvent system;

[0019] d1) mixing the corrosion inhibitor coated metal particles with the organic solvent system and stirring the mixture to obtain a metal solder paste.

[0020] In another embodiment, the method for preparing the metal solder paste comprises the following steps:

[0021] a2) performing a deoxidation treatment on the metal particles to obtain deoxidized metal particles;

[0022] b2) mixing the deoxidized metal particles, the coating agent and the organic solvent, ultrasonicating, centrifuging and washing to obtain coated metal particles;

[0023] c2) mixing the dispersant, diluent and thermosetting adhesive in parts by mass and stirring to obtain an additive system;

[0024] d2) mixing the coated metal particles with the auxiliary agent system and stirring to obtain a metal solder paste.

[0025] In steps a1) and a2), the metal particles are selected from silver particles or copper particles, preferably silver particles. The metal particles are in the form of flakes or spheres; when the metal particles are spherical, the particle size of the metal particles is 100-1000 nm, preferably 300-1000 nm, for example, 300 nm, 400 nm, 500 nm, 800 nm, 1000 nm; when the metal particles are in the form of flakes, the size of the metal particles is 1000-2000 nm, for example, 1000 nm, 1500 nm, 2000 nm.

[0026] The deoxidation treatment includes: the deoxidation treatment includes: first placing the metal particles in a hypophosphorous acid solution, a hypochlorous acid solution or a dilute hydrochloric acid solution, ultrasonically pickling and centrifuging, and then placing the metal particles in anhydrous ethanol, ultrasonically cleaning and centrifuging; more specifically, first placing the metal particles in a 1-2 mol / L hypophosphorous acid solution, a 1-3 mol / L hypochlorous acid solution or a 3-5 mol / L dilute hydrochloric acid solution, ultrasonically pickling for 10-20 minutes and then centrifuging at 4000-6000r / min, and then placing the metal particles in anhydrous ethanol, ultrasonically cleaning for 5-10 minutes and then centrifuging at 2000-3000r / min.

[0027] In step b1), the corrosion inhibitor is selected from at least one of malic acid and tartaric acid; preferably, the corrosion inhibitor includes malic acid and tartaric acid, and the mass ratio of malic acid to tartaric acid is (1-3):1; the organic solvent is anhydrous ethanol, and the mass ratio of the deoxidized metal particles, the corrosion inhibitor and the organic solvent is (75-80):(2-5):(15-23), preferably (75-80):(3-5):(15-23); in step b2), the coating agent is selected from polyvinylpyrrole At least one of alkanone, polyvinyl alcohol and polyacrylic acid; the organic solvent is anhydrous ethanol, and the mass ratio of the deoxidized metal particles, the coating agent and the anhydrous ethanol is (4-5): (3-4): (1-3); in steps b1) and b2), the ultrasonic time is 15-30min, and after ultrasonic treatment, the mixture is centrifuged at 3000-5000r / min, then placed in anhydrous ethanol, ultrasonically cleaned for 5-10min, and then centrifuged at 2000-3000r / min.

[0028] In step c1), the antioxidant is selected from at least one of citric acid, succinic acid, lactic acid, oxalic acid and ascorbic acid, preferably citric acid or succinic acid; the organic solvent is selected from at least one of ethylene glycol, diethylene glycol, terpineol, glycerol and n-decanol; preferably, the organic solvent comprises ethylene glycol, terpineol and n-decanol, and the mass ratio of ethylene glycol, terpineol and n-decanol is 1:(1-2):1; the mass ratio of the antioxidant to the organic solvent in the organic solvent system is (1-3):(97-99), preferably (1-2):(98-99); in step c2), the dispersant is selected from at least one of n-decanol, methanol, cyclohexanol and ethanol, preferably ethanol, cyclohexanol and n-decanol. at least one of decanols; the diluent is selected from at least one of ethylene glycol, propylene glycol, glycerol, n-butanol, diethylene glycol, acetol and polyethylene glycol, preferably at least one of ethylene glycol, propylene glycol and glycerol; the thermosetting adhesive is selected from at least one of melamine formaldehyde resin, furan resin, polybutadiene resin and silicone resin, preferably at least one of furan resin, silicone resin and polybutadiene resin; the mass ratio of the dispersant, the diluent and the thermosetting adhesive in the auxiliary agent system is (1.5-2.5): (95.5-98): (0.5-2); in steps c1) and c2), the stirring is magnetic stirring, and the stirring time is 20-40 min.

[0029] In step d1), the mass ratio of the corrosion inhibitor coated metal particles to the organic solvent system is (80-85):(15-20); in steps d1) and d2), the stirring is magnetic stirring, and the stirring time is 15-30 minutes.

[0030] In step S2, a metal solder paste is coated on the single-sided metallization layer of the copper sheet by coating or printing, and the coating thickness is controlled to be 50-200 μm and the thickness is uniform; after coating, it is placed in a drying furnace and dried under an inert or reducing atmosphere, the inert atmosphere is an atmosphere of nitrogen, argon, etc., and the reducing atmosphere is an atmosphere of formic acid, platinum-catalyzed formic acid, nitrogen and hydrogen mixed gas, etc. The heating rate of the drying process is 2-50°C / min, preferably 10-40°C / min, the drying temperature is 100-200°C, preferably 120-140°C, and the drying time is 2-60min, preferably 10-20min. After drying, a pre-sintered metal film with a thickness of 25-150 μm is formed on the surface of the copper sheet, and the thickness of the pre-sintered metal film is preferably 25-50 μm.

[0031] In step S3, cleaning includes: soaking the copper sheet with the pre-sintered metal film in anhydrous ethanol for 10-15 minutes; and drying by natural drying or using clean hot air at 60-80°C.

[0032] The activation treatment includes: soaking the copper sheet for the first time in a phosphoric acid solution or a citric acid solution, and then washing and drying; wherein the mass content of the phosphoric acid solution is 10-20%, the mass content of the citric acid solution is 5-10%, and the first soaking time is 5-10 minutes; after the first soaking is completed, take out the copper sheet, rinse it with clean water and dry it naturally.

[0033] To enhance the coating effect, the activation treatment also includes: soaking the copper sheet for a second time in a sodium sulfate solution, and then washing and drying it; wherein the mass content of the sodium sulfate solution is 5-10%, and the second soaking time is 5-10 minutes; after the second soaking is completed, take out the copper sheet, rinse it with deionized water, and dry it naturally or use clean hot air to dry it at 60-80°C.

[0034] In step S4, the coating solution includes a first organic matter and a second organic matter, the first organic matter is selected from at least one of diethyl phthalate, dibutyl phthalate, butyl acetate, dimethyl terephthalate, dioctyl phthalate, ethyl propionate, phenyl acetate, isopentyl acetate, and dipropyl phthalate, and the second organic matter is selected from at least one of ethanol, acetone, and ethyl acetate; the mass ratio of the first organic matter to the second organic matter in the coating solution is (3-20): (80-95).

[0035] In one embodiment, the coating solution comprises the following components by mass: 5-10 parts of diethyl phthalate, 2-5 parts of dibutyl phthalate, 2-5 parts of butyl acetate and 80-90 parts of ethanol; preferably, the coating solution comprises the following components by mass: 8 parts of diethyl phthalate, 3 parts of dibutyl phthalate, 4 parts of butyl acetate and 85 parts of ethanol. The preparation method of the above coating solution is as follows: weigh each component by mass, first add diethyl phthalate to a mixing container, then add dibutyl phthalate, add butyl acetate after magnetic stirring for 5-10 minutes, continue magnetic stirring for 5-10 minutes, and then gradually add ethanol, continue stirring while adding ethanol, until all components are completely dissolved to obtain a uniform coating solution.

[0036] In another embodiment, the coating solution comprises the following components by mass: 5-10 parts of dimethyl terephthalate, 1-3 parts of dioctyl phthalate, 2-5 parts of ethyl propionate and 85-95 parts of acetone; preferably, the coating solution comprises the following components by mass: 6 parts of dimethyl terephthalate, 2 parts of dioctyl phthalate, 3 parts of ethyl propionate and 89 parts of acetone. The preparation method of the above coating solution is as follows: weigh each component according to mass, first add dimethyl terephthalate to the mixing container, then add dioctyl phthalate, add ethyl propionate after magnetic stirring for 5-10 minutes, continue magnetic stirring for 5-10 minutes, then gradually add acetone, continue stirring while adding acetone, until all components are completely dissolved to obtain a uniform coating solution.

[0037] In another embodiment, the coating solution comprises the following components by mass: 1-5 parts of phenyl acetate, 1-5 parts of isoamyl acetate, 1-5 parts of dipropyl phthalate and 85-95 parts of ethyl acetate; preferably, the coating solution comprises the following components by mass: 4 parts of phenyl acetate, 3 parts of isoamyl acetate, 4 parts of dipropyl phthalate and 89 parts of ethyl acetate. The preparation method of the above coating solution is as follows: weigh each component by mass, first add phenyl acetate to a mixing container, then add isoamyl acetate, add dipropyl phthalate after magnetic stirring for 5-10 minutes, continue magnetic stirring for 5-10 minutes, then add ethyl acetate, and continue stirring until all components are completely dissolved to obtain a uniform coating solution.

[0038] The coating can be carried out by immersion, spraying or coating. When the immersion method is used, the activated copper sheet is slowly immersed in the coating solution to ensure that the surface of the activated copper sheet is completely in contact with the coating solution, and it is slowly taken out after staying for 2-5 minutes. When the spraying method is used, the coating solution is evenly sprayed on the surface of the activated copper sheet using a spray gun, and attention is paid to the uniformity of the spraying. When the coating method is used, a clean brush is used to evenly apply the coating solution on the surface of the activated copper sheet.

[0039] Curing can be carried out by natural drying, hot air drying or oven curing. When natural drying is used, the coated copper sheet is dried naturally in a clean environment for 1-2 hours; when hot air drying is used, the coated copper sheet is accelerated to dry in clean hot air at 60-80℃ for 30-60 minutes to ensure uniform curing of the film layer; when oven curing is used, the coated copper sheet is cured in an oven at 100-120℃ for 30-60 minutes; when curing, the curing temperature and time are flexibly adjusted according to the thickness and heat resistance of the film layer.

[0040] After curing, the coated copper sheet can be processed into a specified shape by laser cutting or stamping, and then the processed coated copper sheet can be placed on the blue film surface for storage.

[0041] The present invention also provides a coated copper sheet for interconnecting copper electrodes on the front side of a chip, which is prepared according to the above preparation method.

[0042] The present invention also provides a method for interconnecting the above-mentioned coated copper sheet and a chip, comprising the following steps:

[0043] A) Place the chip on a heating platform and heat it to the thermal paste process temperature;

[0044] B) The suction head is heated to the thermal bonding process temperature, and the coated copper sheet is pressurized and thermally bonded to the front of the chip using the heated suction head, and then placed in a sintering furnace for sintering to obtain a power device packaging structure.

[0045] Specifically, in step A), the heat attach process temperature is 100-130°C, preferably 110-130°C; in step B), the heat attach pressure is 1-5MPa, preferably 3-5MPa; the heat attach time is 0.1-2s, preferably 1-2s; the sintering temperature is 200-300°C, preferably 250-270°C; the sintering pressure is 5-20MPa, preferably 5-15MPa; the sintering time is 1-30min, preferably 3-15min.

[0046] The present invention performs single-sided metallization treatment on the bare copper sheet, thereby improving the adhesion between the metal film and the copper sheet; adopts a metal solder paste with a specific composition, which can provide sufficient adhesion between the coated copper sheet and the chip during the sintering process, and does not need to use a temporary fixing agent for dispensing and fixing; by activating and coating the copper sheet with the pre-sintered metal film, a thin, uniform and dense organic protective film is formed on the surface of the coated copper sheet, which not only improves the storage stability of the coated copper sheet, but also does not affect the electrical and thermal conductivity of the coated copper sheet, thereby reducing the packaging cost and improving the service reliability of the packaged device. DETAILED DESCRIPTION

[0047] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.

[0048] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0049] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] Example 1

[0051] 1. Preparation of silver solder paste

[0052] 1) Deoxidation treatment

[0053] Silver particles with a flaky morphology and a size of 1500 nm were placed in a 2 mol / L hypophosphorous acid solution, ultrasonically pickled for 15 minutes, and then centrifuged at 5000 r / min. The silver particles were then placed in anhydrous ethanol, ultrasonically cleaned for 10 minutes, and then centrifuged at 3000 r / min to obtain deoxidized silver particles.

[0054] 2) Corrosion inhibitor coating

[0055] 3 parts of tartaric acid and 1 part of malic acid were uniformly mixed according to mass proportion to obtain a corrosion inhibitor.

[0056] 75 parts of the deoxidized silver particles prepared in step 1), 3 parts of the corrosion inhibitor prepared above and 23 parts of anhydrous ethanol were mixed by mass, ultrasonically treated for 25 minutes, centrifuged at 4000 r / min, then placed in anhydrous ethanol, ultrasonically cleaned for 10 minutes, and centrifuged at 2500 r / min to obtain corrosion inhibitor-coated silver particles.

[0057] 3) Preparation of organic solvent system

[0058] 1 part of ethylene glycol, 1 part of terpineol and 1 part of n-decanol were uniformly mixed according to mass fractions to obtain a mixed organic solvent.

[0059] 2 parts of citric acid, an antioxidant, and 98 parts of the mixed organic solvent prepared above were mixed by weight, and magnetically stirred at room temperature for 30 minutes to obtain an organic solvent system.

[0060] 4) Preparation of silver solder paste

[0061] 80 parts of the corrosion inhibitor-coated silver particles prepared in step 2) were mixed with 20 parts of the organic solvent system prepared in step 3) by mass, and magnetically stirred at room temperature for 25 minutes to obtain a silver solder paste.

[0062] 2. Preparation of Coated Copper Sheet

[0063] 1) Surface treatment

[0064] A bare copper sheet with a thickness of 70 μm, a hardness of 100 HV, and a material of red copper is immersed in a dilute sulfuric acid solution with a mass content of 2%, and taken out after immersion for 15 minutes. Then, the bare copper sheet is immersed in anhydrous ethanol, and taken out after immersion for 5 minutes. Then, the bare copper sheet is immersed in deionized water, and taken out after immersion for 5 minutes. After repeating 3 times, it is dried in a nitrogen atmosphere at 50° C. for 40 minutes to obtain a surface-treated bare copper sheet.

[0065] 2) Single-sided metallization

[0066] The surface-treated bare copper sheet prepared in step 1) is subjected to single-sided metallization treatment to obtain a copper sheet with an Ag coating, wherein the thickness of the Ag coating is 1 μm.

[0067] 3) Apply silver solder paste

[0068] The silver solder paste prepared in step 1 is coated on the Ag coating of the copper sheet prepared in step 2) by printing, and the coating thickness of the silver solder paste is controlled to be about 100 μm and the thickness is uniform. After coating, the silver solder paste is placed in a drying furnace.

[0069] 4) Drying

[0070] The copper sheet coated with the silver solder paste in step 3) was dried in a nitrogen atmosphere, the heating rate during drying was 10°C / min, the drying temperature was 120°C, the drying time was 20min, and after drying, a copper sheet having a pre-sintered silver film on the surface was obtained, and the thickness of the pre-sintered silver film was 50μm.

[0071] The copper sheet with the pre-sintered silver film on the surface was immersed in anhydrous ethanol for 10 minutes, and then dried at 70° C. using clean hot air.

[0072] 5) Activation treatment

[0073] The copper sheet treated in step 4) is placed in a phosphoric acid solution with a mass content of 15% and immersed for 8 minutes. After immersion, the copper sheet is taken out, rinsed with clean water and dried naturally.

[0074] The naturally dried copper sheet was placed in a sodium sulfate solution with a mass content of 6% and immersed for 6 minutes. After immersion, the copper sheet was taken out, rinsed with deionized water and dried naturally.

[0075] 6) Preparation of coating solution

[0076] The coating solution includes the following components in mass fractions: 8 parts of diethyl phthalate, 3 parts of dibutyl phthalate, 4 parts of butyl acetate and 85 parts of ethanol.

[0077] Weigh each component according to mass, first add diethyl phthalate into the mixing container, then add dibutyl phthalate, add butyl acetate after magnetic stirring for 8 minutes, continue magnetic stirring for 8 minutes, then gradually add ethanol, continue stirring while adding ethanol, until all components are completely dissolved to obtain a uniform coating solution.

[0078] 7) Coating and curing

[0079] The copper sheet treated in step 5) is slowly immersed in the coating solution prepared in step 6) by immersion method to ensure that the surface of the copper sheet is completely in contact with the coating solution. After staying for 5 minutes, it is slowly taken out and dried in clean hot air at 70°C for 30 minutes to uniformly solidify the film layer to obtain a coated copper sheet.

[0080] The coated copper sheet is processed into a specified shape by laser cutting and then placed on the blue film surface for storage.

[0081] 3. Interconnection between coated copper sheet and chip

[0082] Place the chip on a heating platform and heat it to the thermal paste process temperature of 130°C.

[0083] Heat the suction head to the thermal bonding process temperature of 130°C, use the heated suction head to remove the coated copper sheet prepared in step 2 from the blue film, and then pressurize and thermally bond it to the front side of the chip. The thermal bonding pressure is 3MPa and the thermal bonding time is 1s.

[0084] The chip with the film-coated copper sheet was placed in a sintering furnace and sintered for 3 minutes at a sintering temperature of 250° C. and a sintering pressure of 10 MPa to obtain a power device packaging structure.

[0085] Example 2

[0086] 1. Preparation of copper solder paste

[0087] 1) Deoxidation treatment

[0088] Spherical copper particles with a particle size of 1000 nm were placed in a 1 mol / L hypophosphorous acid solution, ultrasonically pickled for 20 minutes, and then centrifuged at 6000 r / min. The copper particles were then placed in anhydrous ethanol, ultrasonically cleaned for 5 minutes, and then centrifuged at 2500 r / min to obtain deoxidized copper particles.

[0089] 2) Corrosion inhibitor coating

[0090] 1 part of tartaric acid and 1 part of malic acid were uniformly mixed according to mass proportions to obtain a corrosion inhibitor.

[0091] 75 parts of the deoxidized copper particles prepared in step 1), 5 parts of the corrosion inhibitor prepared above and 20 parts of anhydrous ethanol were mixed by mass, ultrasonically treated for 30 minutes, centrifuged at 5000 r / min, placed in anhydrous ethanol, ultrasonically cleaned for 10 minutes, and centrifuged at 3000 r / min to obtain corrosion inhibitor-coated copper particles.

[0092] 3) Preparation of organic solvent system

[0093] 1 part of ethylene glycol, 1 part of terpineol and 1 part of n-decanol were uniformly mixed according to mass fractions to obtain a mixed organic solvent.

[0094] 1 part of antioxidant citric acid and 99 parts of the mixed organic solvent prepared above were mixed by mass, and magnetically stirred at room temperature for 40 minutes to obtain an organic solvent system.

[0095] 4) Preparation of copper solder paste

[0096] 85 parts of the corrosion inhibitor-coated copper particles prepared in step 2) and 15 parts of the organic solvent system prepared in step 3) were mixed by mass, and magnetically stirred at room temperature for 30 minutes to obtain a copper solder paste.

[0097] 2. Preparation of Coated Copper Sheet

[0098] 1) Surface treatment

[0099] A bare copper sheet with a thickness of 70 μm, a hardness of 100 HV, and a material of red copper is immersed in a dilute sulfuric acid solution with a mass content of 5%, and taken out after immersion for 10 minutes. Then, the bare copper sheet is immersed in anhydrous ethanol, and taken out after immersion for 3 minutes. Then, the bare copper sheet is immersed in deionized water, and taken out after immersion for 3 minutes. After repeating 3 times, it is dried in a nitrogen atmosphere at 60° C. for 20 minutes to obtain a surface-treated bare copper sheet.

[0100] 2) Single-sided metallization

[0101] The surface-treated bare copper sheet prepared in step 1) is subjected to single-sided metallization treatment to sequentially form a Ni plating layer, a Pd plating layer and an Au plating layer (collectively referred to as a Ni / Pd / Au plating layer) on the surface of the bare copper sheet; wherein the thickness of the Ni plating layer is 1.8 μm, the thickness of the Pd plating layer is 0.2 μm, the thickness of the Au plating layer is 1 μm, and the total thickness of the Ni / Pd / Au plating layer is 3 μm.

[0102] 3) Apply copper solder paste

[0103] The copper solder paste prepared in step 1 is coated on the Ag coating of the copper sheet prepared in step 2) by printing, and the coating thickness of the copper solder paste is controlled to be about 100 μm and the thickness is uniform. After coating, the copper solder paste is placed in a drying oven.

[0104] 4) Drying

[0105] The copper sheet coated with copper solder paste in step 3) was dried in a nitrogen atmosphere, the heating rate during drying was 40°C / min, the drying temperature was 140°C, the drying time was 10min, and after drying, a copper sheet with a pre-sintered copper film on the surface was obtained, and the thickness of the pre-sintered copper film was 50μm.

[0106] The copper sheet with the pre-sintered copper film on the surface prepared above was immersed in anhydrous ethanol for 10 minutes, and then taken out of the immersion and dried at 70° C. using clean hot air.

[0107] 5) Activation treatment

[0108] The copper sheet treated in step 4) is placed in a phosphoric acid solution with a mass content of 10% and immersed for 10 minutes. After immersion, the copper sheet is taken out, rinsed with clean water and dried naturally.

[0109] The naturally dried copper sheet was placed in a sodium sulfate solution with a mass content of 10% and soaked for 5 minutes. After soaking, the copper sheet was taken out, rinsed with deionized water and dried naturally.

[0110] 6) Preparation of coating solution

[0111] The coating solution includes the following components by mass: 4 parts of phenyl acetate, 3 parts of isoamyl acetate, 4 parts of dipropyl phthalate and 89 parts of ethyl acetate.

[0112] Weigh each component by mass, first add phenyl acetate into the mixing container, then add isoamyl acetate, add dipropyl phthalate after magnetic stirring for 10 minutes, continue magnetic stirring for 5 minutes, then add ethyl acetate, and continue stirring until all components are completely dissolved to obtain a uniform coating solution.

[0113] 7) Coating and curing

[0114] The copper sheet treated in step 5) is slowly immersed in the coating solution prepared in step 6) by immersion method to ensure that the surface of the copper sheet is completely in contact with the coating solution. After staying for 5 minutes, it is slowly taken out and dried in clean hot air at 70°C for 30 minutes to uniformly solidify the film layer to obtain a coated copper sheet.

[0115] The coated copper sheet is processed into a specified shape by laser cutting and then placed on the blue film surface for storage.

[0116] 3. Interconnection between coated copper sheet and chip

[0117] Place the chip on a heating platform and heat it to the thermal paste process temperature of 120°C.

[0118] Heat the suction head to the thermal bonding process temperature of 120°C, use the heated suction head to remove the coated copper sheet prepared in step 2 from the blue film, and then pressurize and thermally bond it to the front side of the chip. The thermal bonding pressure is 3MPa and the thermal bonding time is 1.5s.

[0119] The chip with the film-coated copper sheet was placed in a sintering furnace and sintered for 10 minutes at a sintering temperature of 260° C. and a sintering pressure of 15 MPa to obtain a power device packaging structure.

[0120] Example 3

[0121] 1. Preparation of silver solder paste

[0122] 1) Deoxidation treatment

[0123] Spherical silver particles with a particle size of 300 nm were placed in a 5 mol / L dilute hydrochloric acid solution, ultrasonically pickled for 10 minutes, and then centrifuged at 4000 r / min. The copper particles were then placed in anhydrous ethanol, ultrasonically cleaned for 10 minutes, and then centrifuged at 2000 r / min to obtain deoxidized silver particles.

[0124] 2) Corrosion inhibitor coating

[0125] 1 part of tartaric acid and 1 part of malic acid were uniformly mixed according to mass proportions to obtain a corrosion inhibitor.

[0126] 80 parts of the deoxidized silver particles prepared in step 1), 5 parts of the corrosion inhibitor prepared above and 15 parts of anhydrous ethanol were mixed by mass, ultrasonically treated for 15 minutes, centrifuged at 3000 r / min, then placed in anhydrous ethanol, ultrasonically cleaned for 5 minutes, and centrifuged at 2000 r / min to obtain corrosion inhibitor-coated silver particles.

[0127] 3) Preparation of organic solvent system

[0128] 1 part of ethylene glycol, 2 parts of terpineol and 1 part of n-decanol were uniformly mixed according to mass fractions to obtain a mixed organic solvent.

[0129] 2 parts of succinic acid, an antioxidant, and 98 parts of the mixed organic solvent prepared above were mixed by mass, and magnetically stirred at room temperature for 20 minutes to obtain an organic solvent system.

[0130] 4) Preparation of silver solder paste

[0131] 82 parts of the corrosion inhibitor-coated silver particles prepared in step 2) were mixed with 18 parts of the organic solvent system prepared in step 3) by mass, and magnetically stirred at room temperature for 15 minutes to obtain a silver solder paste.

[0132] 2. Preparation of Coated Copper Sheet

[0133] 1) Surface treatment

[0134] A bare copper sheet with a thickness of 100 μm, a hardness of 120 HV, and a material of oxygen-free copper is immersed in a dilute sulfuric acid solution with a mass content of 4%, and taken out after immersion for 10 minutes. Then, the bare copper sheet is immersed in anhydrous ethanol, and taken out after immersion for 3 minutes. Then, the bare copper sheet is immersed in deionized water, and taken out after immersion for 3 minutes. After repeating 3 times, it is dried in a nitrogen atmosphere at 60° C. for 20 minutes to obtain a surface-treated bare copper sheet.

[0135] 2) Single-sided metallization

[0136] The surface-treated bare copper sheet prepared in step 1) is subjected to single-sided metallization treatment to sequentially form a Ni coating and an Ag coating (collectively referred to as a Ni / Ag coating) on ​​the surface of the bare copper sheet; wherein the thickness of the Ni coating is 2 μm, the thickness of the Ag coating is 1 μm, and the total thickness of the Ni / Ag coating is 3 μm.

[0137] 3) Apply silver solder paste

[0138] The silver solder paste prepared in step 1 is coated on the Ag coating of the copper sheet prepared in step 2) by printing, and the coating thickness of the silver solder paste is controlled to be about 50 μm and the thickness is uniform. After coating, it is placed in a drying furnace.

[0139] 4) Drying

[0140] The copper sheet coated with the silver solder paste in step 3) was dried in a nitrogen atmosphere, the heating rate during drying was 20°C / min, the drying temperature was 140°C, the drying time was 10min, and after drying, a copper sheet having a pre-sintered silver film on the surface was obtained, and the thickness of the pre-sintered silver film was 25μm.

[0141] The copper sheet with the pre-sintered copper film on the surface prepared above was immersed in anhydrous ethanol for 10 minutes, and then taken out of the immersion and dried at 70° C. using clean hot air.

[0142] 5) Activation treatment

[0143] The copper sheet treated in step 4) is placed in a phosphoric acid solution with a mass content of 20% and immersed for 5 minutes. After immersion, the copper sheet is taken out, rinsed with clean water and dried naturally.

[0144] The naturally dried copper sheet was placed in a sodium sulfate solution with a mass content of 5% and immersed for 10 minutes. After immersion, the copper sheet was taken out, rinsed with deionized water and dried naturally.

[0145] 6) Preparation of coating solution

[0146] The coating solution includes the following components by mass: 6 parts of dimethyl terephthalate, 2 parts of dioctyl phthalate, 3 parts of ethyl propionate and 89 parts of acetone.

[0147] Weigh each component according to mass, first add dimethyl terephthalate into the mixing container, then add dioctyl phthalate, add ethyl propionate after magnetic stirring for 5 minutes, continue magnetic stirring for 10 minutes, then gradually add acetone, continue stirring while adding acetone until all components are completely dissolved to obtain a uniform coating solution.

[0148] 7) Coating and curing

[0149] The copper sheet treated in step 5) is slowly immersed in the coating solution prepared in step 6) by immersion method to ensure that the surface of the copper sheet is completely in contact with the coating solution. After staying for 2 minutes, it is slowly taken out and dried in clean hot air at 70°C for 30 minutes to uniformly solidify the film layer to obtain a coated copper sheet.

[0150] The coated copper sheet is processed into a specified shape by laser cutting and then placed on the blue film surface for storage.

[0151] 3. Interconnection between coated copper sheet and chip

[0152] Place the chip on a heating platform and heat it to the thermal paste process temperature of 110°C.

[0153] Heat the suction head to the thermal bonding process temperature of 110°C, use the heated suction head to remove the coated copper sheet prepared in step 2 from the blue film, and then pressurize and thermally bond it to the front side of the chip. The thermal bonding pressure is 5MPa and the thermal bonding time is 2s.

[0154] The chip with the film-coated copper sheet was placed in a sintering furnace and sintered for 15 minutes at a sintering temperature of 270° C. and a sintering pressure of 5 MPa to obtain a power device packaging structure.

[0155] Example 4

[0156] Except for the difference in preparing the silver solder paste in step 1, the rest is the same as that in Example 1; the preparation method of the silver solder paste of this embodiment is as follows:

[0157] 1) Deoxidation treatment

[0158] Silver particles with a flaky morphology and a size of 1500 nm were placed in a 2 mol / L hypophosphorous acid solution, ultrasonically pickled for 15 minutes, and then centrifuged at 5000 r / min. The silver particles were then placed in anhydrous ethanol, ultrasonically cleaned for 10 minutes, and then centrifuged at 3000 r / min to obtain deoxidized silver particles.

[0159] 2) Coating with coating agent

[0160] 40 parts of the deoxidized silver particles prepared in step 1), 30 parts of the coating agent polyvinyl pyrrolidone and 30 parts of anhydrous ethanol were mixed by mass, ultrasonically treated for 25 minutes, centrifuged at 4000 r / min, then placed in anhydrous ethanol, ultrasonically cleaned for 10 minutes, and centrifuged at 2500 r / min to obtain coated silver particles.

[0161] 3) Preparation of auxiliary agent system

[0162] 1.5 parts of cyclohexanol as a dispersant, 98 parts of ethylene glycol as a diluent, and 0.5 parts of furan resin as a thermosetting adhesive were mixed, and magnetically stirred at room temperature for 30 minutes to obtain an auxiliary agent system.

[0163] 4) Preparation of silver solder paste

[0164] 15 parts of the coated silver particles prepared in step 2) and 85 parts of the auxiliary agent system prepared in step 3) were mixed by mass, and magnetically stirred at room temperature for 25 minutes to obtain a silver solder paste.

[0165] Comparative Example 1

[0166] Except that in step 2 of preparing the coated copper sheet, the single-sided metallization treatment in step 2) is not performed, that is, no Ag plating layer is provided, but silver solder paste is directly coated on the surface-treated bare copper sheet, the rest is the same as in Example 1.

[0167] Comparative Example 2

[0168] Except that step 5) activation treatment is not performed in step 2 for preparing the coated copper sheet, that is, the copper sheet treated in step 4) is directly immersed in the coating solution for coating, the rest is the same as Example 1.

[0169] Comparative Example 3

[0170] The process is the same as in Example 1 except that in step 5) of preparing the coated copper sheet in step 2, only a 15% by mass phosphoric acid solution is used for the first immersion, and a 6% by mass sodium sulfate solution is not used for the second immersion.

[0171] Comparative Example 4

[0172] Except that step 6) and step 7) are not performed in step 2 for preparing the coated copper sheet, the rest is the same as in Example 1.

[0173] Comparative Example 5

[0174] The process is the same as that of Example 4 except that the coating with the coating agent in step 2) is not performed and the coating agent polyvinyl pyrrolidone is directly added to the auxiliary agent system in step 3) in the same amount.

[0175] Test Example 1

[0176] The following method is used to test the coated copper sheet after thermal bonding and the coated copper sheet after sintering:

[0177] Thermal paste shedding rate: the probability of natural falling of the coated copper sheet after testing 100 thermal pastes;

[0178] Average thrust of thermal paste: the average thrust when the coated copper sheets after 30 thermal pastes are pushed horizontally until they fall off;

[0179] Sintering average shear strength: Test the ratio of the average thrust when 30 sintered coated copper sheets are pushed horizontally until they fall off to the force-bearing area.

[0180] The results are shown in Table 1.

[0181] Table 1

[0182]

[0183] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a coated copper sheet for interconnecting copper electrodes on the front side of a chip, characterized in that: The steps include: S1: performing surface treatment and single-sided metallization treatment on the bare copper sheet to obtain a copper sheet with a single-sided metallization layer; S2: coating a metal solder paste on a single-sided metallization layer of the copper sheet, and then drying it in an inert or reducing atmosphere to obtain a copper sheet with a pre-sintered metal film; S3: cleaning, drying and activating the copper sheet with the pre-sintered metal film to obtain an activated copper sheet; S4: coating the activated copper sheet with a coating solution, and curing the coated copper sheet to obtain a coated copper sheet for interconnecting the copper electrodes on the front side of the chip.

2. The preparation method according to claim 1, characterized in that: In step S1, the surface treatment includes: soaking the bare copper sheet in dilute sulfuric acid solution, anhydrous ethanol and deionized water in sequence, repeating 2-3 times and then drying in an inert atmosphere; Preferably, the single-sided metallization layer is an Ag coating, a Ni / Ag coating or a Ni / Pd / Au coating; Preferably, the thickness of the single-sided metallization layer is 1-3 μm.

3. The preparation method according to claim 1, characterized in that: In step S2, the method for preparing the metal solder paste comprises the following steps: a) performing a deoxidation treatment on the metal particles to obtain deoxidized metal particles; b) mixing the deoxidized metal particles, the corrosion inhibitor and the organic solvent, ultrasonicating, centrifuging and washing to obtain the corrosion inhibitor-coated metal particles; c) mixing an antioxidant and an organic solvent and stirring to obtain an organic solvent system; d) mixing the corrosion inhibitor coated metal particles with the organic solvent system and stirring the mixture to obtain a metal solder paste.

4. The preparation method according to claim 3, characterized in that: In step a), the deoxidation treatment comprises: first placing the metal particles in a hypophosphorous acid solution, a hypochlorous acid solution or a dilute hydrochloric acid solution, ultrasonically cleaning and then centrifuging, and then placing the metal particles in anhydrous ethanol, ultrasonically cleaning and then centrifuging; Preferably, in step b), the corrosion inhibitor is selected from at least one of malic acid and tartaric acid; the organic solvent is anhydrous ethanol; the mass ratio of the deoxidized metal particles, the corrosion inhibitor and the organic solvent is (75-80): (2-5): (15-23); Preferably, in step c), the antioxidant is selected from at least one of citric acid, succinic acid, lactic acid, oxalic acid and ascorbic acid; the organic solvent is selected from at least one of ethylene glycol, diethylene glycol, terpineol, glycerol and n-decanol; and the mass ratio of the antioxidant to the organic solvent in the organic solvent system is (1-3): (97-99); Preferably, in step d), the mass ratio of the corrosion inhibitor coated metal particles to the organic solvent system is (80-85):(15-20).

5. The preparation method according to claim 1, characterized in that: In step S2, the thickness of the pre-sintered metal film is 25-150 μm; Preferably, the heating rate during drying is 2-50° C. / min, the drying temperature is 100-180° C., and the drying time is 2-60 min.

6. The preparation method according to claim 1, characterized in that: In step S3, the activation treatment includes: soaking the copper sheet for the first time in a phosphoric acid solution or a citric acid solution, and then washing and drying after soaking; Preferably, the mass content of the phosphoric acid solution is 10-20%, and the mass content of the citric acid solution is 5-10%; the first soaking time is 5-10 minutes; Preferably, the activation treatment further comprises: soaking the copper sheet for a second time in a sodium sulfate solution, and washing and drying after soaking; Preferably, the mass content of the sodium sulfate solution is 5-10%; and the second soaking time is 5-10 minutes.

7. The preparation method according to claim 1, characterized in that: In step S4, the coating solution includes a first organic substance and a second organic substance, the first organic substance is selected from at least one of diethyl phthalate, dibutyl phthalate, butyl acetate, dimethyl terephthalate, dioctyl phthalate, ethyl propionate, phenyl acetate, isopentyl acetate, and dipropyl phthalate, and the second organic substance is selected from at least one of ethanol, acetone, and ethyl acetate; Preferably, the mass ratio of the first organic matter to the second organic matter in the coating solution is (3-20): (80-95).

8. A coated copper sheet for interconnecting copper electrodes on the front side of a chip, characterized in that: Prepared according to the preparation method described in any one of claims 1 to 7.

9. The method for interconnecting a coated copper sheet and a chip according to claim 8, characterized in that: The steps include: A) Place the chip on a heating platform and heat it to the thermal paste process temperature; B) The suction head is heated to the thermal bonding process temperature, and the coated copper sheet is pressurized and thermally bonded to the front of the chip using the heated suction head, and then placed in a sintering furnace for sintering to obtain a power device packaging structure.

10. The interconnection method according to claim 9, characterized in that: In step A), the thermal bonding process temperature is 100-130°C; Preferably, in step B), the heat application pressure is 1-5 MPa, and the heat application time is 0.1-2 s; the sintering temperature is 200-300° C., the sintering pressure is 5-20 MPa, and the sintering time is 1-30 min.

Citation Information

Patent Citations

  • Copper paste for power device packaging and preparation and chip mounting method thereof

    CN117727722A

  • Plastic package type SiC power module with pressed silver sintering on two sides

    CN117913060A

  • Surface preparation of metal sheet to be coated

    JP1990104674A

Cited By

  • Composite metal soldering lug and preparation method and application thereof

    CN121535396A

  • Metal soldering lug and preparation method and application thereof

    CN121715732A